Association between COVID-19 vaccination and critical outcomes among older adults with dementia: a comparative cohort study - Radomyslsky, Zorian; Kivity, Sara; Lidar, Shira; Bentur, Netta; Korn, Liat; Nissanholtz-Gannot, Rachel; Sternberg, Shelley; Halevi Hochwald, Inbal; Reges, Orna; Alon, Yaniv; Saban, Mor (Frontiers in Public Health, 2023)
As COVID-19 vaccines became available, understanding their potential benefits in vulnerable populations has gained significance. This study explored the advantages of COVID-19 vaccination in individuals with cognitive disorders by analyzing health-related variables and outcomes.A prospective cohort study analyzed electronic medical records of 25,733 older adults with cognitive disorders and 65,544 older adults without cognitive disorders from March 2020 to February 2022. COVID-19 vaccination status was the primary exposure variable, categorized as fully vaccinated or unvaccinated. The primary outcomes measured were all-cause mortality and hospitalization rates within 14 days and 400 days postvaccination. Data on vaccination status, demographics, comorbidities, testing history, and clinical outcomes were collected from electronic health records. The study was ethically approved by the relevant medical facility's Institutional Review Board (0075-22-MHS).RESULTS: Vaccinated individuals had significantly lower mortality rates in both groups. In